2008
DOI: 10.1007/s10228-008-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Inter-populational difference in microsatellite–centromere map distances in the loach, Misgurnus anguillicaudatus

Abstract: Microsatellite-centromere recombination rates were estimated at 21 loci in relation to centromere of chromosomes in gynogenetic diploid lines induced from loaches of two different populations in Japan. All the microsatellite loci gave allelic segregation according to the Mendelian manner of inheritance in normal diploid families. Since loaches from Kita population in the southern area of Hokkaido Island and those from Memanbetsu population in the northern area, Hokkaido, Japan, were reported to be genetically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…As discussed above, the inter‐populational hybrid males in the loach demonstrated the reproductive capacity that often observed in interspecific hybrids of other fish species, as in the previous studies on hybrid females (Arias‐Rodriguez et al., 2009a). Thus, parental populations may be genetically distinct to the level of inter‐specific differences, which give rise to the occurrence of aberrant reproductive manner.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As discussed above, the inter‐populational hybrid males in the loach demonstrated the reproductive capacity that often observed in interspecific hybrids of other fish species, as in the previous studies on hybrid females (Arias‐Rodriguez et al., 2009a). Thus, parental populations may be genetically distinct to the level of inter‐specific differences, which give rise to the occurrence of aberrant reproductive manner.…”
Section: Discussionsupporting
confidence: 76%
“…The loach Misgurnus anguillicaudatus (Teleostei:Cobitidae) has been identified as a single species entity in Japanese populations (Saitoh, 1989). However, recent genetic studies suggest the presence of genetically diversified groups within this species, based on the analyses of allozymes variations (Khan and Arai, 2000), microsatellite DNA markers (Arias‐Rodriguez et al., 2007), sequences of the mitochondrial DNA control region (Morishima et al., 2008), and microsatellite‐centromere recombination map distances (Arias‐Rodriguez et al., 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…No definite study has yet concluded whether these two clades are from a same species or not. However, at least at this stage, Arias-Rodriguez et al (2009) showed that there existed significant difference between the two in microsatellite-centromere map distances on chromosomes. In this study we presumed the two clades as separated biological units according to Morishima et al (2008) and Arias-Rodriguez et al (2009).…”
Section: Discussionmentioning
confidence: 88%
“…Subclade B2 is distributed around Kanto region (middle of Japan) and haplotypes of the same lineage have been found in China (Morishima et al 2008;Koizumi 2009). Clade A is genetically closer to related species such as M. fossilis and M. mizolepis as apposed to Clade B, and thus the two clades were suggested as different species (Morishima et al 2008;Arias-Rodriguez et al 2009). On the other hand natural triploid and asexually reproducing clonal diploid loaches have been reported at low rates in Japan (0-16%; average: 1.4%) (Zhang and Arai 1999).…”
Section: Introductionmentioning
confidence: 96%